2016
DOI: 10.1158/0008-5472.can-15-2841
|View full text |Cite
|
Sign up to set email alerts
|

A Novel MIF Signaling Pathway Drives the Malignant Character of Pancreatic Cancer by Targeting NR3C2

Abstract: Pancreatic cancers with aberrant expression of macrophage migration inhibitory factor (MIF) are particularly aggressive. To identify key signaling pathways that drive disease aggressiveness in tumors with high MIF expression, we analyzed the expression of coding and non-coding genes in high and low MIF-expressing tumors in multiple cohorts of pancreatic ductal adenocarcinoma (PDAC) patients. The key genes and pathways identified were linked to patient survival and were mechanistically, functionally and clinica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
311
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(325 citation statements)
references
References 28 publications
7
311
0
Order By: Relevance
“…In colorectal cancer, some studies have demonstrated that decreased MR expression is associated with increased microvascular density and poor patient survival through the direct inhibition of dysregulated VEGFA expression (Di Fabio et al, ; Tiberio et al, ). Similar results have also been demonstrated in early stage cervical carcinoma (Huang et al, ), pancreatic cancer (Yang et al, ), breast cancer (Nan, Dorgan, & Rebbeck, ), and lung cancer (Jeong et al, ). All of the publications mentioned above illustrate that NR3C2 might function as an onco‐suppressor gene in various cancer types.…”
Section: Discussionsupporting
confidence: 75%
“…In colorectal cancer, some studies have demonstrated that decreased MR expression is associated with increased microvascular density and poor patient survival through the direct inhibition of dysregulated VEGFA expression (Di Fabio et al, ; Tiberio et al, ). Similar results have also been demonstrated in early stage cervical carcinoma (Huang et al, ), pancreatic cancer (Yang et al, ), breast cancer (Nan, Dorgan, & Rebbeck, ), and lung cancer (Jeong et al, ). All of the publications mentioned above illustrate that NR3C2 might function as an onco‐suppressor gene in various cancer types.…”
Section: Discussionsupporting
confidence: 75%
“…In line with what has been described,13 high cytoplasmic DYRK1B expression was detected in PDAC and PanIN lesions (H-score, n=7: 254.6±21.58) (supplementary figure S1A). DYRK1A mRNA was also increased in PDAC samples as compared with normal adjacent tissue in two inhouse sample sets, and in an independent cohort studied from publicly available microarray data (GSE62452)23 (figure 1B,C). Differential expression of DYRK1B mRNA was only observed in one set of samples (supplementary figure S1B,C).…”
Section: Resultsmentioning
confidence: 94%
“…For instance, overexpression of NR3C2 inhibits cell proliferation, colony formation, invasion, migration, and tubular formation of renal cell carcinoma in vitro and in vivo (15). Yang et al (25) also showed that NR3C2 inhibited epithelial-tomesenchymal transition and cell invasion in pancreatic cancer. In this study, we found that NR3C2 was the target gene of miR-766 and that NR3C2 attenuated miR-766-midiated proliferation, colony formation, invasion, and migration of HCC cells by regulating the b-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%